Turkey as partner of the EU in the refugee crisis: Ankara's problems and interests - Günter Seufert (Stiftung Wissenschaft und Politik (SWP), 2016)
Rarely has a resolution by the European Union heads of state and government been criticised from such diverse perspectives and positions of vested interest as the EU's agreements with the Turkish government of 29th November 2015 regarding the alleviation of the refugee crisis. Eastern European states, human rights organisations, a European public critical of Turkey and Turkish intellectuals are united in their skeptical rejection of Brussels' policies. They take the view that the EU's financial and political concessions to Turkey have overstepped the mark. By contrast, the situation in Turkey has barely played any part in the discussion to date. Little interest has been shown in the financial means at Turkey's disposal in order to fulfil these tasks, in the political cost which would arise for the government as a result of steps taken in the above-mentioned direction and in the major upheaval in Turkish asylum and aliens policy which is inevitably associated with the agreements. Also lacking is speculation on why Turkey is prepared to cooperate with the European Union at all, how it could have been persuaded to participate in such a collaboration initially and on which mutual objectives and interests a cooperation of this nature could be based. (SWP Comments)
Keywords: 320